A biOI-loaded enteromorpha biochar composite material, a preparation method and application thereof

CN122912884APending Publication Date: 2026-10-16FIRST INSTITUTE OF OCEANOGRAPHY MNR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611067028.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,单相BiOI存在光生载流子复合率高、比表面积小及易光腐蚀等问题,严重制约其实际应用

Benefits of technology

[0015]本发明的有益效果是:通过独特结构设计,BiOI均匀负载于PBC表面并暴露(110)高能晶面,显著增加活性位点密度与比表面积。该复合结构兼具高吸附容量与高效载流子迁移特性。此过程中,吸附作用与自由基/非自由基协同效应共同促进了污染物快速矿化为CO2与H2O,实现了吸附耦合光催化高效降解有机污染物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912884A_ABST
    Figure CN122912884A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of environmental materials, in particular to a kind of loaded BiOI's enteromorpha biological carbon composite material and its preparation method and application.The present application proposes the concept of "pollution control with waste", innovatively combines enteromorpha biological carbon (PBC) with photocatalyst BiOI, constructs BiOI@PBC heterojunction composite material with oxygen vacancy (OV) regulation, aims at synergistically strengthening the adsorption enrichment and photocatalytic degradation ability of pollutants.By solvothermal method, BiOI nanosheet is in-situ grown on the surface of PBC, the porous structure of PBC is used to inhibit the agglomeration of BiOI, induce BiOI preferentially grow along the high-activity (110) crystal surface, and by introducing OV, the energy band structure of the material is further regulated, the visible light absorption is enhanced, and the carrier separation is promoted, realizing the efficient degradation of various organic pollutants, with excellent stability and reusability.The present application uses marine waste enteromorpha as raw material, realizes the resource high-value utilization, the preparation process is simple, environment-friendly, and is suitable for the rapid and efficient removal of organic pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental materials technology, specifically to a BiOI-loaded biochar composite material of Ulva prolifera, its preparation method, and its application. Background Technology

[0002] The widespread use and discharge of organic pollutants, especially antibiotics (such as tetracycline (TC)), has posed a serious challenge to global water environment security. Statistics show that global annual antibiotic consumption exceeds 100,000 tons, of which approximately 30%-90% enters the aquatic environment as parent organisms or metabolites, inducing the spread and accumulation of antibiotic resistance genes (ARGs), severely threatening ecosystem stability and human health. Traditional water treatment technologies such as biodegradation and coagulation sedimentation have limited efficiency in removing recalcitrant antibiotics and easily generate toxic byproducts. While advanced oxidation processes (AOPs) based on peroxymonosulfate (PMS) can achieve efficient mineralization of pollutants by generating reactive oxygen species (ROS), they rely on transition metal activators (such as Co). 2+ Fe 3+ The characteristics of biochar make it prone to secondary pollution. In recent years, the rise of non-metallic activation strategies has provided new ideas for the greening of AOPs (Alternative Organic Pollutants), among which biochar (BC) has attracted much attention due to its rich surface functional groups, tunable electronic structure, and environmentally friendly properties. The periodic outbreaks of marine green tides of Ulva prolifera have become an ecological disaster in the Yellow Sea and East China Sea of ​​my country, but its high cellulose content, low ash content, and unique sulfonated polysaccharide structure make it an ideal precursor for the preparation of high-performance biochar. Studies have shown that Ulva prolifera biochar (PBC) has a hierarchical porous structure, high specific surface area, and rich oxygen / nitrogen functional groups. It can not only efficiently enrich pollutants through π-π interactions, hydrogen bonding, and electrostatic adsorption, but also act as an electron shuttle to activate PMS to generate various ROS. However, the catalytic activity of single biochar is still limited by problems such as low carrier migration rate and poor ROS selectivity. Therefore, constructing "adsorption-catalysis" bifunctional materials by combining semiconductor photocatalysts with biochar has become an important strategy to improve the efficiency of pollutant degradation.

[0003] BiOI is a typical layered structure p [Bi₂O₂] is a type of semiconductor characterized by its narrow bandgap, strong visible light absorption, and unique properties. 2+Interlayer polarization has shown significant advantages in photocatalysis. However, single-phase BiOI suffers from high recombination rates of photogenerated carriers, small specific surface area, and susceptibility to photocorrosion, severely limiting its practical application. To address these challenges, this invention proposes a sustainable development concept of "treating pollution with waste," innovatively combining PBC and BiOI to construct a BiOI@PBC heterojunction composite material with oxygen vacancy (OVs) regulation, aiming to synergistically enhance the adsorption, enrichment, and photocatalytic degradation capabilities of pollutants. The study utilizes a solvothermal method to grow BiOI nanosheets in situ on the PBC surface, leveraging the porous structure of PBC to inhibit BiOI aggregation and induce preferential growth of BiOI along the highly active (110) crystal plane. Furthermore, by introducing OVs, the band structure of the material is further regulated, enhancing visible light absorption and promoting carrier separation. Summary of the Invention

[0004] The purpose of this invention is to provide a BiOI-loaded biochar composite material of Ulva prolifera, its preparation method, and its application.

[0005] The technical solution adopted in this invention is: (1) Preparation of seaweed biochar (PBC): seaweed powder was calcined at 300~700 ℃ for 3~6 h under inert gas, and then ball-milled after cooling to obtain activated biochar; (2) Preparation of BiOI@PBC: Bi(NO3)3∙5H2O was added to ethylene glycol to prepare a Bi(NO3)3 precursor solution, and then NaI was added to ethylene glycol to prepare a NaI precursor solution. Subsequently, pretreated PBC was added to the Bi(NO3)3 precursor solution at a certain mass, and then the loaded PBC-Bi(NO3)3 mixed solution was introduced dropwise into the NaI precursor solution. After a stable colloidal mixed solution was formed, it was transferred to a polytetrafluoroethylene high-pressure reactor and heated at a certain temperature for several hours to complete crystal growth and interface coupling. The final product was purified by centrifugation and dried to obtain BiOI-supported Ulva prolifera biochar composite material (BiOI@PBC).

[0006] Preferably, the seaweed powder is calcined at 300-500 °C for 3-6 h under an inert gas atmosphere.

[0007] Preferably, the mass of Bi(NO3)3∙5H2O is 1.5~2.5 g, and the mass of NaI is 0.3~0.8 g.

[0008] Preferably, the Bi(NO3)3 solution and NaI solution are subjected to ultrasonic dispersion and magnetic stirring for 20-60 min under nitrogen protection.

[0009] Preferably, the pretreated PBC is added to the Bi(NO3)3 solution in a mass fraction gradient of 30-100%, and the surface pre-modification is completed by stirring continuously at room temperature for 1-3 h.

[0010] Preferably, the PBC-Bi(NO3)3 mixed solution is introduced dropwise into the NaI solution. After a stable colloidal mixed solution is formed, it is transferred to a polytetrafluoroethylene high-pressure reactor and heated at 120~200 ℃ for 8~20 h to complete crystal growth and interface coupling.

[0011] A BiOI@PBC composite material was prepared by the above method.

[0012] A method for remediating antibiotic-contaminated sediments includes the following steps: dispersing the above-mentioned BiOI@PBC into 25 mL of antibiotic-contaminated ultrapure water, and treating the wastewater using a 300~700 W xenon lamp light source to simulate visible light irradiation conditions.

[0013] Preferably, the dosage of BiOI@PBC is 5.0 mg.

[0014] Preferably, during the treatment of tetracycline (TC) contaminated sediments, 1 mL of suspension is sampled at time points of 0, 15, 30, 45, 60, and 90 min.

[0015] The beneficial effects of this invention are as follows: Through a unique structural design, BiOI is uniformly loaded onto the PBC surface and exposed with a (110) high-energy crystal plane, significantly increasing the density of active sites and specific surface area. This composite structure possesses both high adsorption capacity and efficient carrier migration characteristics. In this process, adsorption and the synergistic effect of free radicals / non-free radicals jointly promote the rapid mineralization of pollutants into CO2 and H2O, achieving highly efficient degradation of organic pollutants through adsorption-coupled photocatalysis.

[0016] Specifically: (1) The BiOI@PBC of the present invention successfully constructed a composite photocatalyst with abundant oxygen vacancies and high-energy crystal face exposure through an improved solvothermal method. It can efficiently degrade organic pollutants by working together with the synergistic effect of free radicals / non-free radicals. (2) The ·O2 generated by BiOI@PBC in the photocatalytic reaction of BiOI@PBC-2 according to the present invention - with h + It is the main active species for degrading TC; (3) The present invention uses seaweed powder as raw material to prepare BiOI@PBC, which not only realizes the resource utilization of marine waste biomass, but also creates certain economic value. Attached Figure Description

[0017] Figure 1 This is the X-ray diffraction (XRD) pattern of the sample.

[0018] Figure 2 Field emission scanning electron microscope (FESEM) image of BiOI@PBC-2.

[0019] Figure 3 High-resolution transmission electron microscope (HRTEM) image of BiOI@PBC-2.

[0020] Figure 4 Degradation experiments of TC with different BiOI@PBC dosages.

[0021] Figure 5 Photocatalytic degradation of TC by BiOI@PBC in a cycling experiment. Detailed Implementation

[0022] The present invention will be further explained and described below with reference to specific embodiments.

[0023] Example 1

[0024] A BiOI@PBC preparation method includes the following steps: (1) After drying and pulverizing the seaweed, pass it through a 20-mesh sieve to obtain seaweed powder; (2) The BiOI@PBC composite material was prepared by a solvothermal method combined with an in-situ loading process. The specific synthesis route is as follows: First, the prepared functionalized porous PBC was ball-milled to obtain active powder. 1.94 g Bi(NO3)3∙5H2O was added to 30 mL of ethylene glycol to prepare a Bi(NO3)3 precursor solution, and then 0.45 g NaI was added to 30 mL of ethylene glycol to prepare a NaI precursor solution. The solutions were ultrasonically dispersed and magnetically stirred for 30 min under nitrogen protection. Subsequently, the pretreated PBC was added to the Bi(NO3)3 precursor solution in batches according to a 66% mass fraction gradient. The solution was stirred continuously at room temperature for 2 h to complete the surface pre-modification. Then, the PBC-Bi(NO3)3 mixed solution was introduced dropwise into the NaI precursor solution. After a stable colloidal mixed solution was formed, it was transferred to a 100 mL polytetrafluoroethylene high-pressure reactor and crystal growth and interface coupling were completed at 160 ℃ for 16 h. The final product, after centrifugation purification and drying, was labeled as BiOI@PBC-2.

[0025] Performance testing: (1) The XRD pattern of the BiOI@PBC material in this embodiment is as follows: Figure 1 As shown.

[0026] Depend on Figure 1It can be seen that the biochar of Ulva prolifera exhibits a graphitic carbon structure in the composite material, proving that the prepared BiOI@PBC composite material has good crystallinity.

[0027] (2) In this embodiment, the microstructure of BiOI@PBC was studied using the FESEM system, such as... Figure 2 As shown.

[0028] Depend on Figure 2 It can be seen that the morphology of BiOI undergoes a significant transformation. The morphology of BiOI changes from a sheet-like structure to a smaller blocky structure, and it grows densely on the PBC surface in a vertical orientation, indicating that the interfacial bonding between the two is enhanced, providing abundant active sites and mass transfer channels for photocatalytic reactions.

[0029] (3) The HRTEM spectrum of BiOI@PBC-2 in this embodiment is as follows: Figure 3 As shown.

[0030] Depend on Figure 3 Further analysis of the microstructure of BiOI@PBC by HRTEM revealed obvious, continuous and well-defined lattice fringes on the surface of BiOI@PBC, with a plane spacing of 0.27 nm, corresponding to the (110) crystal plane of BiOI. The results were consistent with the XRD pattern.

[0031] (4) This embodiment presents degradation experiments of TC by different materials, such as... Figure 4 As shown.

[0032] Depend on Figure 4 It can be seen that by constructing the BiOI@PBC composite system, the BiOI@PB composite materials all exhibit significantly enhanced TC degradation performance. Compared with the monomer materials, the adsorption efficiency of the composite system is significantly improved in the dark reaction stage, while it continues to show stable TC degradation ability in the light reaction stage.

[0033] (5) This embodiment is a photocatalytic degradation TC cycle experiment of BiOI@PBC, such as Figure 5 As shown.

[0034] Depend on Figure 5 It can be seen that after five cycles of reuse, BiOI@PBC still maintains a degradation efficiency of over 88.3% for TC (100% degradation rate on the first use), with only an 11.7% performance degradation, indicating that it has excellent cycle stability and structural durability.

[0035] Example 2

[0036] A BiOI@PBC preparation method includes the following steps: (1) After drying and pulverizing the seaweed, pass it through a 20-mesh sieve to obtain seaweed powder; (2) The BiOI@PBC composite material was prepared by a solvothermal method combined with an in-situ loading process. The specific synthesis route is as follows: First, the prepared functionalized porous PBC was ball-milled to obtain active powder. 1.94 g Bi(NO3)3∙5H2O was added to 30 mL of ethylene glycol to prepare a Bi(NO3)3 precursor solution, and then 0.45 g NaI was added to 30 mL of ethylene glycol to prepare a NaI precursor solution. The solutions were ultrasonically dispersed and magnetically stirred for 30 min under nitrogen protection. Subsequently, the pretreated PBC was added to the Bi(NO3)3 precursor solution in batches according to a 33% mass fraction gradient. The surface was pre-modified by stirring continuously at room temperature for 2 h. Then, the PBC-Bi(NO3)3 mixed solution was introduced dropwise into the NaI precursor solution. After a stable colloidal mixed solution was formed, it was transferred to a 100 mL polytetrafluoroethylene high-pressure reactor and crystal growth and interface coupling were completed at 160 ℃ for 16 h. The final product, after centrifugation purification and drying, was labeled as BiOI@PBC-1.

[0037] The BiOI@PBC-1 prepared in this embodiment was highly similar in morphology to the BiOI@PBC-2 in Example 1. Under the same conditions (pH=7), the degradation rate of TC in the solution decreased. The degradation rate decreased from 88.3% to 65.5% after 15 minutes and from 98.3% to 79.2% after 60 minutes, but still maintained good degradation performance.

[0038] Example 3: A BiOI@PBC preparation method includes the following steps: (1) After drying and pulverizing the seaweed, pass it through a 20-mesh sieve to obtain seaweed powder; (2) The BiOI@PBC composite material was prepared by a solvothermal method combined with an in-situ loading process. The specific synthesis route is as follows: First, the prepared functionalized porous PBC was ball-milled to obtain active powder. 1.94 g Bi(NO3)3∙5H2O was added to 30 mL of ethylene glycol to prepare a Bi(NO3)3 precursor solution, and then 0.45 g NaI was added to 30 mL of ethylene glycol to prepare a NaI precursor solution. The solutions were ultrasonically dispersed and magnetically stirred for 30 min under nitrogen protection. Subsequently, the pretreated PBC was added to the Bi(NO3)3 precursor solution in batches according to a 100% mass fraction gradient. The solution was stirred continuously at room temperature for 2 h to complete the surface pre-modification. Then, the PBC-Bi(NO3)3 mixed solution was introduced dropwise into the NaI precursor solution. After a stable colloidal mixed solution was formed, it was transferred to a 100 mL polytetrafluoroethylene high-pressure reactor and crystal growth and interface coupling were completed at 160 ℃ for 16 h. The final product, after centrifugation purification and drying, was labeled as BiOI@PBC-3.

[0039] The BiOI@PBC-3 prepared in this example was highly similar in morphology to the BiOI@PBC-2 in Example 1. Under the same conditions (pH=7), the degradation rate of TC decreased slightly, from 88.3% to 80.3% after 15 minutes and from 98.3% to 81.1% after 60 minutes, but still maintained good degradation performance.

[0040] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A bismuth iodide oxide-supported biochar photocatalytic composite material, characterized in that, The bismuth iodide oxide supported biochar photocatalytic composite material comprises a biochar support and bismuth iodide semiconductors grown in situ on the support surface. The biochar support is Ulva prolifera-based porous biochar (PBC). BiOI nanosheets are vertically loaded on the surface of Ulva prolifera biochar, preferentially exposing the high-energy BiOI (110) crystal plane. The material is rich in oxygen vacancies (OVs) to form a heterojunction interface. The BiOI is grown in situ with a theoretical loading mass fraction of 30% to 100% of Ulva prolifera biochar. The composite material is synthesized in situ by solvothermal in situ. HRTEM characterization shows that the lattice fringe spacing is 0.27 nm, corresponding to the BiOI (110) crystal plane. The composite material has dual functions of pollutant adsorption and enrichment and visible light photocatalytic degradation. After five cycles of use, the degradation efficiency of tetracycline remains above 88.3%.

2. A bismuth iodide oxide-supported biochar photocatalytic composite material according to claim 1, characterized in that, Includes the following steps: Preparation of Ulva prolifera biochar PBC: Ulva prolifera was dried, pulverized and sieved to obtain Ulva prolifera powder, which was calcined at 300~700 ℃ for 3~6 h in an inert atmosphere, cooled and ball-milled to obtain porous activated Ulva prolifera biochar; Preparation of dual precursor solutions: Dissolve 1.5~2.5g Bi(NO3)3・5H2O in ethylene glycol to obtain Bi(NO3)3 precursor solution, and dissolve 0.3~0.8g NaI in ethylene glycol to prepare NaI precursor solution; under nitrogen protection, the two precursor solutions are ultrasonically and magnetically stirred separately. Biochar surface pre-modification: Pretreated PBC was added to Bi(NO3)3 precursor solution at a mass fraction of 30%~100% of the theoretical BiOI yield, and the surface was modified by stirring continuously at room temperature for 1~3 h to obtain PBC-Bi(NO3)3 mixed solution. Solventothermal in-situ composite: PBC-Bi(NO3)3 mixed solution was added dropwise to NaI precursor solution, stirred until a stable colloid was formed, and then transferred to a polytetrafluoroethylene reactor. The mixture was kept at 120~200 ℃ for 8~20 h to complete the growth of BiOI crystals and the coupling of the heterojunction interface, and the reaction product was obtained. Post-processing: The reaction product was centrifuged, washed, and dried to obtain the BiOI@PBC composite material.

3. The method according to claim 2, characterized in that, In step (1), the calcination temperature of the seaweed is 300~500℃, and the seaweed powder is passed through a 20-mesh sieve.

4. The method according to claim 2, characterized in that, In step (2), the amount of Bi(NO3)3・5H2O used is 1.94 g, the amount of NaI used is 0.45 g, and the amount of ethylene glycol solvent is 30 mL each.

5. The method according to claim 2, characterized in that, Step (3) The mass fraction of PBC is 33%, 66% or 100%; Step (4) The solvothermal conditions are 160 ℃ and kept at that temperature for 16 h.

6. The application of the bismuth iodide oxide-supported biochar photocatalytic composite material according to claim 1, characterized in that: The composite material was used to prepare an antibiotic remediation agent for water bodies; the application method was visible light synergistic adsorption-photocatalysis combined degradation of tetracycline antibiotic pollutants in water bodies.

7. The application according to claim 6, characterized in that, The application method is as follows: BiOI@PBC is dispersed in antibiotic-contaminated water and treated with visible light irradiation using a 300~700 W xenon lamp; the material dosage is 5.0 mg BiOI@PBC per 25 mL of contaminated water, and the pollutant degradation effect is detected by sampling at regular intervals within 0~90 min to achieve efficient mineralization removal of antibiotics.

8. The application according to claim 7, characterized in that, During the treatment of tetracycline (TC) contaminated sediments, 1 mL of suspension was sampled at time points of 0, 15, 30, 45, 60, and 90 min.